Improving Product Quality Under the Integrated Relationship Between Attribute Based Costing and Process Reengineering Techniques: A Review Article - Suhad Abdul Meer Kadhim; Fatimah Flayyih Oudah; Nihro Jabal Afloogee (International Journal of Economics, Management and Accounting, 2025)
As a result of rapid technological progress, increased competition, and the global opening of markets, local markets have been flooded with a large number of foreign products of superior quality compared to local products. This has exposed Iraqi economic units to numerous pressures for various reasons, most notably the high cost of their products and the low quality of their products. This requires these units to seek solutions that lead to the provision of a high-quality product capable of competing with foreign products in terms of price and quality, thereby achieving customer satisfaction. Therefore, the research aims to integrate the two techniques of Attribute Based Costing and process reengineering and to demonstrate their role in improving product quality. The researcher reached a set of conclusions, the most important of which are The weakness of the costing system applied at the research sample factory, its failure to accurately monitor and identify cost elements throughout the product lifecycle, and the management's lack of interest and awareness in implementing contemporary costing techniques and their role in improving the quality of its products, thus ensuring their sustainability. The integration of specifications-based costing with process reengineering technology has added substantial improvements to product specifications, aligning them with customer requirements and needs, and leading to improved product quality.